Salmonella Oranienburg Isolated from Horses, Wild Turkeys and An Edible Home Garden Fertilized with Raw Horse Manure. (20th February 2013) - Jay‐Russell, M. T.; Madigan, J. E.; Bengson, Y.; Madigan, S.; Hake, A. F.; Foley, J. E.; Byrne, B. A.
Summary In July 2010, a horse from a rural farm (Farm A) in coastal Northern California was diagnosed with Salmonella Oranienburg infection following referral to a veterinary hospital for colic surgery. Environmental sampling to identify potential sources and persistence of Salmonella on the farm was conducted from August 2010 to March 2011. Salmonella was cultured using standard enrichment and selective plating. Pure colonies were confirmed by biochemical analysis, serotyped and compared by pulsed‐field gel electrophoresis (PFGE) analysis. A total of 204 clinical and environmental samples at Farm A were analysed, and Salmonella spp. was isolated from six of eight (75%) horses, an asymptomatic pet dog, two of seven (28.6%) water samples from horse troughs, nine of 20 (45%) manure storage pile composites, 16 of 71 (22.5%) wild turkey faeces and four of 39 (10.3%) soil samples from the family's edible home garden. Well water and garden vegetable samples and horse faecal samples from a neighbouring ranch were negative. S. Oranienburg with a PFGE pattern indistinguishable from the horse clinical strain was found in all positive sample types on Farm A. The investigation illustrates the potential for widespread dissemination of Salmonella in a farm environment following equine infections. We speculate that a recent surge in the wild turkey population on the property could have introduced S. Oranienburg into the herd, although we cannot rule out the possibility wild turkeys were exposed on the farm or to other potential sources of Salmonella. Findings from the investigation indicated that raw horse manure applied as fertilizer was the most likely source of garden soil contamination. Viable S. Oranienburg persisted in garden soil for an estimated 210 days, which exceeds the 120‐day standard between application and harvest currently required by the National Organic Program. The study underscores the need to educate the public about potential food safety hazards associated with using raw animal manure to fertilize edible home gardens.